Prevalence and associated factors of diarrhea among under-five children in the Jawi district, Awi Zone Ethiopia, 2019. Community based comparative cross-sectional study - Gessesse, Dereje Nibret; Tarekegn, Abebe Aynalem (Frontiers in Pediatrics, 2022)
Abstract Introduction: Even though most diarrheal deaths are preventable using simple and low-cost interventions still diarrheal death accounts for 1 in 9 of all child deaths worldwide. This makes it the second leading cause of death among under-five children. Therefore, this study is aimed to assess the prevalence of diarrhea and associated factors among children of age under five in Jawi district, Awi Zone, Ethiopia. Method: Community-based comparative cross-sectional study design was conducted from March to June 2019 and a total of 440 study participants were included in the study. Data was collected using a pre-tested face-to-face interviewer-administered questionnaire. The data was entered into EPI info version 7 and then exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regression was fitted to assess independent association with the dependent variables. The significant association was declared using Adjusted Odds Ration at 95% confidence level with p-value less than or equal to 0.05. Result: The overall prevalence of diarrhea in the study district was 15.5%. The occurrence of diarrheal diseases morbidity among model and non-model HHs was 10.9% and 20% respectively. Shallow water [AOR: 6.12, 95%CI; (1.52, 24.58)], and maternal diarrhea [AOR: 4.11, 95%CI; (1.75, 9.61)] were factors associated with childhood diarrhea. Place of birth [OR: 2.52, 95%CI (1.16, 5.49)] and maternal diarrhea [AOR: 3.50; 95%CI (1.28, 9.56)] in non-model households were significantly associated with childhood diarrhea in the study area. Conclusion: The overall proportion of childhood diarrhea was found to be high. Thus, to decrease childhood diarrhea in the study area, the health extensions better to educate the community on how to dispose of solid and liquid wastes, the pit they are going to use for waste disposal, and for mothers how to handle if they get a diarrheal disease. Concerned stakeholders, also better to promote institutional delivery and to give access to the community for safe water.